2001
DOI: 10.1182/blood.v97.10.3259
|View full text |Cite
|
Sign up to set email alerts
|

Short-chain fatty acid derivatives stimulate cell proliferation and induce STAT-5 activation

Abstract: Current chemotherapeutic and butyrate therapeutics that induce fetal hemoglobin expression generally also suppress erythropoiesis, limiting the production of cells containing fetal hemoglobin (F cells). Recently, selected short-chain fatty acid derivatives (SCFADs) were identified that induce endogenous ␥-globin expression in K562 cells and human burst-forming units-erythroid and that increase proliferation of human erythroid progenitors and a multilineage interleukin-3-dependent hematopoietic cell line. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
96
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 64 publications
(100 citation statements)
references
References 79 publications
4
96
0
Order By: Relevance
“…Structural studies have revealed the presence of a previously unrecognized fatty acid docked in the ligand-binding domain of HNF4α [31,32], consistent with the finding that fatty acids regulate HNF4α-dependent gene expression [52,53]. Fatty acids may also modulate STAT5 activity [54,55]. We therefore investigated whether fatty acids could modulate the inhibitory cross-talk between HNF4α and STAT5b.…”
Section: Discussionsupporting
confidence: 64%
“…Structural studies have revealed the presence of a previously unrecognized fatty acid docked in the ligand-binding domain of HNF4α [31,32], consistent with the finding that fatty acids regulate HNF4α-dependent gene expression [52,53]. Fatty acids may also modulate STAT5 activity [54,55]. We therefore investigated whether fatty acids could modulate the inhibitory cross-talk between HNF4α and STAT5b.…”
Section: Discussionsupporting
confidence: 64%
“…To stimulate fetal globin expression, short chain fatty acids (SCFADs) have been used in many experimental therapeutics such as reporter gene assays, transgenic murine, and nonhuman primate models; and in clinical trials (Pace et al 2002;Steinberg and Rodgers 2001;Perrine 2005;Perrine et al 1993;Collins et al 1995;Ikuta et al 1998;Dover, Brusilow, and Charache 1994;Boosalis et al 2001;Vadolas et al 2004;Atweh, Sutton, and Nassif 1999). Sodium phenylbutyrate and arginine butyrate increase total hemoglobin in beta thalassemia patients (Perrine et al 1993;Collins et al 1995;Ikuta et al 1998;Atweh, Sutton, and Nassif 1999;Perrine et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…It has been found that sodium butyrate acts as a histone deacetylase (HDAC) inhibitor and induces gene expression through acetylation of histones, which results in chromatin remodeling [35]. On the other hand, it can alter the phosphorylation state of several proteins including mitogen-activated protein kinase (MAPK) and signal transducer and activator of transcription (STAT)-5 [36,37]. These have been proposed as mechanisms by which sodium butyrate regulates variety of genes, besides its effects on growth arrest and differentiation.…”
Section: Discussionmentioning
confidence: 99%